Pemeriksaan Tekanan Darah, Gula Darah Sewaktu, dan Kolesterol Pada Warga Pra-Lansia Hingga Lansia di Sekitar RT 01 RW 21 Kelurahan Tangkerang Tengah, Kecamatan Marpoyan Damai, Pekanbaru - Bhukkar Adil Sjam; Kahermasari Kahermasari; Arnila Melina; Cherlina Cherlina; Nurmaliza Hasan (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
The prevalence of cardiovascular disease in Indonesia continues to increase and is one of the leading causes of death. Some of the risk factors for cardiovascular disease are hypertension, dyslipidemia and diabetes mellitus. These risk factors are not only experienced by urban communities but also occur in people living in rural areas. The purpose of this activity is to determine the incidence of hypertension, diabetes mellitus and cholesterol.Data collection on cardiovascular disease risk factors was carried out by measuring blood pressure, blood sugar levels and total cholesterol levels. This activity was attended by 40 total respondents with an age range of 40-60 years, 14 men and 26 women. Data analysis showed that 72% of respondents had blood pressure above normal. Respondents with normal blood sugar were only 13%, and the rest needed further examination. Cholesterol levels in the high category were 80% and slightly high were found in 20% of respondents. The data shows that the prevalence of risk factors for cardiovascular disease is quite large in the pre-elderly and elderly community in RT 01 RW 21 Tangkerang Tengah, Marpoyan Damai District, Pekanbaru.